(untitled) (Вісник: Міжнародні відносини, 2024)
South Korea’s economy (hereinafter referred to as “Korea”) has become one of the most diversified and technologically advanced in the world in the past 50 years. Korea began to pursue a broad policy of liberalization towards foreign investments, including foreign direct investment (FDI), and due to well-conducted reforms, governments were able to direct financial flows to the priority areas of economic development of the national economy. FDI began to play an important role in the country’s economy and acted as the main catalyst in the country’s industrial development and technical upgrading of industries. Of particular importance for the development of the country’s national productive capacity is the question of the specific nature of foreign capital penetration forms (contract and contracting forms, creation of joint ventures, although later they gave way to the practice of using mergers and acquisitions) and the establishment of cooperative relations between local companies and foreign subsidiaries of multinational enterprises (MNEs), and this not only increased the productivity of domestic firms, facilitated the transfer of complex management methods and advanced technologies but has also strengthened the industry structure. Cooperation with foreign companies gradually increased the competitiveness of local companies. Korea’s attractiveness in terms of FDI was the result of the country’s rapid economic development and its specialization in new information and communication technologies. The main factors of the country’s effective economic development were the combination of market mechanisms development and active state regulation in all spheres of the economy. It has become important to protect national development priorities and support national exporters in regulation of the activities of foreign investors. However, the government pursued an active policy of attracting foreign investments. One of the tools for attracting additional capital to the country’s economy was the creation of special economic zones (SEZs), in particular export production zones with a favorable tax regime.